2019
DOI: 10.1128/msystems.00191-18
|View full text |Cite
|
Sign up to set email alerts
|

Temperate Bacteriophages from Chronic Pseudomonas aeruginosa Lung Infections Show Disease-Specific Changes in Host Range and Modulate Antimicrobial Susceptibility

Abstract: Temperate bacteriophages are a common feature of Pseudomonas aeruginosa genomes, but their role in chronic lung infections is poorly understood. This study was designed to identify the diverse communities of mobile P. aeruginosa phages by employing novel metagenomic methods, to determine cross infectivity, and to demonstrate the influence of phage infection on antimicrobial susceptibility. Mixed temperate phage populations were chemically mobilized from individual P. aeruginosa, isolated from patients with cys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 55 publications
2
19
0
Order By: Relevance
“…When serial transfer cultures are initiated with mixtures of sensitive E. coli, virulent and temperate phage, l VIR and l + resistant mutants emerge and ascend to dominate the bacterial population, but both temperate and lytic phage continue to persist along with a minority population of newly formed lysogens. The frequency of these newly formed lysogens is markedly increased if, the addition of low concentrations of kanamycin, which selects for the carriage the l KAN prophage [19,43,44] A recent study showed that temperate phage of P. aeruginosa in the lungs of CF patients carries antibiotic resistance genes and relates to the progression of the disease by providing a selective advantage to their host bacteria [45]. Most importantly, the results of these experiments with combinations of lytic and temperate l indicate that a substantial fraction of the resistant bacteria evolving in these populations are lysogens.…”
Section: Discussionmentioning
confidence: 99%
“…When serial transfer cultures are initiated with mixtures of sensitive E. coli, virulent and temperate phage, l VIR and l + resistant mutants emerge and ascend to dominate the bacterial population, but both temperate and lytic phage continue to persist along with a minority population of newly formed lysogens. The frequency of these newly formed lysogens is markedly increased if, the addition of low concentrations of kanamycin, which selects for the carriage the l KAN prophage [19,43,44] A recent study showed that temperate phage of P. aeruginosa in the lungs of CF patients carries antibiotic resistance genes and relates to the progression of the disease by providing a selective advantage to their host bacteria [45]. Most importantly, the results of these experiments with combinations of lytic and temperate l indicate that a substantial fraction of the resistant bacteria evolving in these populations are lysogens.…”
Section: Discussionmentioning
confidence: 99%
“…Mobile genetic elements, on the other hand, can be either parasitic or beneficial, depending on conditions. For example, the acquisition of prophage can alter improve Pseudomonas metabolism and increase competitive ability (16,44), but prophage entry into the lytic cycle leads to cell lysis and death. Similarly, ICE and plasmids carry genes that can allow Pseudomonas to exploit new niches, such as novel metabolites or eukaryotic hosts, or resist stresses, such as heavy metals and antibiotics, but the acquisition of these elements also tends to be associated with costs that can generate selection against carriage (32,(45)(46)(47).…”
Section: Introductionmentioning
confidence: 99%
“…Virulence factors as pyocyanin production, biofilm and motility are regulated by QS and also influenced by the phage infections (Morkunas et al, 2012;Hosseinidoust et al, 2013;Latino et al, 2014;Casta帽eda-Tamez et al, 2018;Tariq et al, 2019). The infection with the wild type phage, AUS531phi, carrying the bci gene, increased the production of virulence factors, pyocyanin and biofilm, whose presence is characteristic in the lung of CF patients (Casta帽eda-Tamez et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The higher pyocyanin production may be due to a protective response to a higher infectivity capacity of the phage AUS531phi. Temperate phages could help P. aeruginosa select for bacterial characteristics that favor persistence of bacteria in the lung (Latino et al, 2014;Tariq et al, 2019). Thus, the bci gene may help clinical isolates of P. aeruginosa to survive in lung infections, increasing their chance of being infected by temperate phages.…”
Section: Discussionmentioning
confidence: 99%